1989
DOI: 10.5962/bhl.part.117765
|View full text |Cite
|
Sign up to set email alerts
|

Comparaison des régimes alimentaires de la fouine (Martes foina Erxl.) et de la martre (Martes martes L.) dans une région du Jura suisse

Abstract: Notes on the Coleoptera Scarabaeoidea in the Museum of Geneva. IV -Three new species of Rhy parus (Aphodiidae), one new species of Eusphaeropeltis and seven new species of Madrasostes (Ceratocanthidae) are described from Sabah. A key is given to the species of the latter, and evolutionary trends of the eye reduction in Ceratocanthidae are discussed.Les Hespérides Saint-Christoly, 4, rue Beaubadat, F-33000 Bordeaux. Marchesi, P et al. 1989. "Comparaison des régimes alimentaires de la fouine (Martes foina Erxl.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 5 publications
1
18
1
1
Order By: Relevance
“…Martes martes and M. foina usually differ only in their habitat preference, as M. martes is considered a forest habitat specialist, while M. foina is a generalist and flexible species, occurring in a wide spectrum of open and forest habitats. Despite this, the two species often occur in sympatry, but scarce evidence of food competition has been found in syntopic populations (Marchesi et al, 1989;Clevenger 1994;Genovesi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Martes martes and M. foina usually differ only in their habitat preference, as M. martes is considered a forest habitat specialist, while M. foina is a generalist and flexible species, occurring in a wide spectrum of open and forest habitats. Despite this, the two species often occur in sympatry, but scarce evidence of food competition has been found in syntopic populations (Marchesi et al, 1989;Clevenger 1994;Genovesi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both the stone marten and the red fox have been shown to be opportunistic species (e.g. Marchesi et al 1989, Cavallini and Lovari 1991, Prigioni 1991, which tend to take what is most available. We think that a combination of reasons (B) and (C) may explain why their diet can be based so extensively on plant food, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Odum 1983), sympatric stone and pine martens are likely to specialise on different food resources to coexist, thus expanding the overall trophic niche of Martes sp. to overlap with that of the fox (Marchesi et al 1989, Cantini 1991. Cantini (1991) concluded that the remarkable dietary similarity between foxes and martens may then be more apparent than actual.…”
Section: Introductionmentioning
confidence: 99%
“…The pine marten Martes martes and the closely related stone marten Martes foina are quite similar in terms of body size, morphology and feeding habits (Goszczynski 1976;Marchesi et al 1989). Their distribution range overlaps across a large part of continental Europe (Proulx et al 2004), the two species showing different habitat preferences.…”
Section: Introductionmentioning
confidence: 97%